Patron-Client Relationships Between Boat Owners and Crew Members in Puger Kulon Village, Jember Regency - Novikarumsari, Nurul Dwi; Hikmah, Mutiara; Sofia, Sofia; Metalisa, Rindi; Rokhani, Rokhani (Faculty of Fisheries and Marine Science, Brawijaya University, 2026)
This study explores the patron-client relations between boat owners and crew members (ABK) in Puger Kulon Village, Jember Regency, focusing on social dynamics, labor hierarchy, and economic dependency in the marine fisheries sector. Boat owners control production tools such as vessels and fishing gear, and hold authority in making operational decisions during fishing trips. Conversely, crew members occupy a subordinate position due to limited access to capital and dependence solely on physical labor for income. However, the patron-client relations observed are not purely one-directional or repressive. There are informal spaces for negotiation and subtle resistance that allow ABK to express their concerns. Using a qualitative descriptive approach, the research employed purposive and snowball sampling to select informants. Data were gathered through in-depth interviews, observation, and documentation, then analyzed using Miles and Huberman’s interactive model. The findings reveal that profit-sharing systems, community norms, and job distribution structures reflect complex and dynamic power relations. The traditional saraan system is used to divide income among crew members based on their roles and contributions. This study shows that power within fishing communities is relational, not absolute, and continuously shaped by everyday social practices.